2017
DOI: 10.1002/iub.1651
|View full text |Cite
|
Sign up to set email alerts
|

A genetic variant in a homocysteine metabolic gene that increases the risk of congenital cardiac septal defects in Han Chinese populations

Abstract: Elevated homocysteine levels are known to be a risk factor for congenital cardiac septal defects (CCSDs), but the mechanism underlying this effect is unknown. The genetic variants that were significantly associated with circulating homocysteine concentrations have been systematically identified through the genome-wide association studies of one-carbon core metabolites. To examine the role of the genome-wide significant homocysteine related variants in the occurrence of CCSDs, we investigated the association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Our study found that increased maternal PA levels caused VSD and ASD phenotypes in mice, which was in accordance with the maternal hyperhomocysteine-induced and GATA4 mutation-induced CHD phenotypes in humans. 42 , 43 , 44 , 45 , 46 These phenomena suggest that PA signals have a crosstalk with homocysteine signals and synergistically regulate GATA4 signals. Besides septal defects, GATA4 mutations have also been reported to be associated with complex CHDs.…”
Section: Discussionmentioning
confidence: 98%
“…Our study found that increased maternal PA levels caused VSD and ASD phenotypes in mice, which was in accordance with the maternal hyperhomocysteine-induced and GATA4 mutation-induced CHD phenotypes in humans. 42 , 43 , 44 , 45 , 46 These phenomena suggest that PA signals have a crosstalk with homocysteine signals and synergistically regulate GATA4 signals. Besides septal defects, GATA4 mutations have also been reported to be associated with complex CHDs.…”
Section: Discussionmentioning
confidence: 98%
“…Although we did not find any significant DMRs associated with DS-CHD after FDR correction, the nominally significant DMRs were enriched for genes implicated in cardiac processes, suggesting that at least some of the DMRs may reflect true epigenetic mechanisms associated with DS-CHD development. In particular, Males Only DMRs selected by machine learning feature selection were able to distinguish CHD from non-CHD samples and frequently mapped to genes associated with CHDs or cardiomyopathies, including FUNDC1 [ 71 ], ETV5 [ 72 , 73 ], SYT9 [ 74 ], CAMTA1 [ 75 ], GRIA4 [ 76 ], and IGF1R [ 77 80 ]. Additionally, DMRs that contributed to enrichment for heart-related gene ontology terms included TNNI3 , a cardiac-specific gene that codes for cardiac troponin I, whose absence leads to severe pediatric cardiomyopathy [ 81 ], and GATA4, which encodes a member of the GATA family of zinc finger transcription factors, are essential for mammalian cardiac development, and whose sequence variants have been identified in individuals with CHDs [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not find any significant DMRs associated with DS-CHD after FDR correction, the nominally significant DMRs were enriched for genes implicated in cardiac processes, suggesting that at least some of the DMRs may reflect true epigenetic mechanisms associated with DS-CHD development. In particular, Males Only DMRs selected by machine learning feature selection were able to distinguish CHD from non-CHD samples and frequently mapped to genes associated with CHDs or cardiomyopathies, including FUNDC1 [71], ETV5 [72,73], SYT9 [74], CAMTA1 [75], GRIA4 [76], and IGF1R [77][78][79][80]. Additionally, DMRs that contributed to enrichment for heart-related gene ontology terms included TNNI3, a cardiac-specific gene that codes for cardiac troponin I, whose absence leads to severe pediatric cardiomyopathy [81], and GATA4, which encodes a member of the GATA family of zinc finger transcription factors, are essential for mammalian cardiac development, and whose sequence variants have been identified in individuals with CHDs [82].…”
Section: Discussionmentioning
confidence: 99%